ANALISIS KEBUTUHAN GURU TERHADAP MEDIA PEMBELAJARAN VIDEO INTERAKTIF DALAM MUATAN IPA (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
This research aims to analyze teachers' needs for interactive video learning media in Natural Sciences (IPA) content in class 6 at SDN 3 Sulahan. The research method used is descriptive qualitative through interview techniques with the class 6 homeroom teacher. The results of the research show that SD N 6 Sulahan has used media in science learning, but it is still simple. In accordance with the results of interviews which stated that there is a great need for media that attracts students' interest in learning, such as interactive video learning media in science learning, which is significant in improving learning and teaching achievement in class 6 at SDN 3 Sulahan.